PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP PRESTASI KERJA APARATUR SIPIL NEGARA - TUPAN, THRESIA NATALIA; Lengkong, Florence Daicy; Kiyai, Burhanuddin (JURNAL ADMINISTRASI PUBLIK, 2017)
In accordance with the issues raised then this study aims as follows: To determine the effect of educationand training on the performance of civil state employment at the Regional Personnel Board Education andResearch town bitung.Education and Training is substantially understood as a process of increasing the potential or ability,competence, and career of the employee / employee concerned. The dimensions of development, in additionto increasing the potential ratios (thought, logic, IQ, competence), also include the improvement of ethicsand morality or spiritual quotience (SQ).The general objectives of education and training programs should be directed towards improvingorganizational productivity. This general objective can be achieved if a specific goal can be realized first.This research is explorative. The results of the study show a significant association of education and trainingon ASN work performance in the Regional Personnel Board, PP Kota Bitung. It can be seen from thecorrelation value of R = 0.68 is close to the maximum correlation coefficient coefficient (1.00) and thecoefficient of determination (R-square) 0,46 has significant development / improvement of ASN workperformance in Badan Kepegawaian Kota Bitung 46 or 0, 46% is determined / influenced by education andtraining variables, while the remaining 54% is determined / influenced by other variables. This means thatthe higher the education and training are done later the ASN work performance is higher. The conclusionsof education and training have been significant on the performance of ASN in Regional Personnel Agency,PP Kota Bitung. Education and training influences on ASN attitudes and behaviors that perform their officetasks.Keywords: Education and training, job performance, State civil apparatus (ASN)